Comparison of Alginate Utilization Pathways in Culturable Bacteria Isolated From Arctic and Antarctic Marine Environments - Cha, Qian-Qian; Wang, Xiu-Juan; Ren, Xue-Bing; Li, Dong; Wang, Peng; Li, Ping-Yi; Fu, Hui-Hui; Zhang, Xi-Ying; Chen, Xiu-Lan; Zhang, Yu-Zhong; Xu, Fei; Qin, Qi-Long (Frontiers in Microbiology, 2021)
Alginate, mainly derived from brown algae, is an important carbon source that can support the growth of marine microorganisms in the Arctic and Antarctic regions. However, there is a lack of systematic investigation and comparison of alginate utilization pathways in culturable bacteria from both polar regions. In this study, 88 strains were isolated from the Arctic and Antarctic regions, of which 60 strains could secrete alginate lyase and reproduce in the medium with alginate as the sole carbon source. These alginate-utilizing strains belong to 9 genera of the phyla Proteobacteria and Bacteroidetes. The genomes of 26 alginate-utilizing strains were further sequenced and genomic analyses show that they all contain the gene clusters related to alginate utilization. The alginate transport systems of Proteobacteria differ from that of Bacteroidetes and there may be unique transport systems among different genera of Proteobacteria. The biogeographic distribution pattern of alginate utilization genes was further investigated. The alginate utilization genes are found to cluster according to bacterial taxonomy rather than geographic location, indicating that the alginate utilization genes do not evolve independently in both polar regions. This study systematically illustrates the alginate utilization pathways in culturable bacteria from the Arctic and Antarctic regions, shedding light into the distribution and evolution of alginate utilization pathways in polar bacteria.